Q: What is -9x - 3 -3x equals 4 plus x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9x + 3 - 6x - 2 = 3x + 1

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

9x+3

3 / 9x+63 / 3(3x+2)1 / 3x+2

9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.

Related questions

9x + 3 - 6x - 2 = 3x + 1

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3

x = 2, y = 3

x + 5 + 3x - 7 + 9x + 3 - 4x Switch the like numbers closer to make the equation easier. x + 3x + 9x - 4x + 5 - 7 + 3 However this is an unsolvable as it isn't an equation. An equation needs an equals sign, for example: x + 3x + 9x - 4x + 5 - 7 + 3 = 0, or x + 3x + 9x - 4x + 5 - 7 + 3 = 10 If it is the former then the answer is 9x = -1 Thus x = -1/9

9x+3

3 / 9x+63 / 3(3x+2)1 / 3x+2

x+5+3x-7+9x+3-4x Collect like terms: 9x+1

3(x2 + 3x + 1)

9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.

(9x + 12) / 3 = 3x+4 ■

Multiply first equation by 3: 9x + 15y = 63Add that and second equation: 19y = 57Divide by 19: y = 3, so x = 2